The Representation of Magical Realism Elements in the Novel Sputnik Sweetheart by Haruki Murakami - Dian Annisa Nur Ridha; Muhamad Ramadhan (Chi e Journal of Japanese Learning and Teaching, 2025)
This study explores the elements of magical realism and the social contexts underlying their emergence in Haruki Murakami’s Sputnik Sweetheart. Drawing on Wendy B. Faris’s theory of magical realism, the analysis employs structural and dialectical approaches. The findings reveal that Sputnik Sweetheart embodies all five defining elements of magical realism. This is exemplified in the mysterious disappearance of Sumire on a small island in Greece, an event unexplainable through realistic logic and instead framed as a transition into another dimension—blurring the boundary between reality and imagination. Similarly, the appearance of Miu’s doppelgänger in her Swiss apartment intensifies the novel’s unsettling magical atmosphere. These events evoke ambiguity about Sumire’s sudden disappearance and Miu’s overnight transformation, as the real and the imaginary intertwine. Beyond identifying these narrative elements, the study also uncovers the social context behind Murakami’s use of magical realism—specifically, the collective trauma and social injustices experienced by marginalized female characters, as well as implicit critiques of Japan’s socio-political relations with its neighboring countries.